GLUTAMINASE FREE L-ASPARAGINASE PRODUCING ENDOPHYTES FROM MANGROVES - G, Salini (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To screen endophytes isolated from mangroves for their potential to produce glutaminase free L-asparaginase . Methods: Endophytes were isolated from leaves and stems of three mangrove plants using surface sterilization technique followed by inoculation of the plant parts in nutrient media. Bacterial and fungal endophytes isolated were tested for production of glutaminase free L-asparaginase by inoculating them in MM9 and MCD media respectively, supplemented with asparagine /glutamine. L-asparaginase activity in glutaminase free L-asparaginase producers was measured by Nesselerization method. Results: Six bacterial endophytes and one fungal endophyte were found to produce glutaminase free L-asparaginase. Highest L-asparaginase activity was shown by bacterial endophytes of the mangrove Sonneratia caseolaris . Conclusion: Endophytes isolated in the present study hold the potential to produce glutaminase free L-asparaginase and they need to be considered further in the search of L-asparaginase with high therapeutic index.